2020
DOI: 10.1084/jem.20200649
|View full text |Cite
|
Sign up to set email alerts
|

Inflammasome signaling in human placental trophoblasts regulates immune defense against Listeria monocytogenes infection

Abstract: The human placenta is a dynamic organ that modulates physiological adaptations to pregnancy. To define the immunological signature of the human placenta, we performed unbiased profiling of secreted immune factors from human chorionic villi isolated from placentas at mid and late stages of pregnancy. We show that placental trophoblasts constitutively secrete the inflammasome-associated cytokines IL-1β and IL-18, which is blocked by NLRP3 inflammasome inhibitors and occurs without detectable gasdermin D cleavage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(84 citation statements)
references
References 52 publications
13
71
0
Order By: Relevance
“…One well-established function of IL-1β in other settings is its capacity to "prime" cells for heightened responses to other stimuli, such as inflammasome-activating factors. Megli and colleagues showed that placental IL-1β production during midgestation is associated with increased IL-1β levels in serum and up-regulated expression of caspase-1 and IL-1β in circulating monocytes (Megli et al, 2020). Conditioned media from chorionic villous explants from pregnant women similarly primed the monocytes of nonpregnant women for up-regulated IL-1β, caspase-1, and NLRP3 expression.…”
Section: Trophoblast Il-1β Primes Maternal Monocytesmentioning
confidence: 99%
See 4 more Smart Citations
“…One well-established function of IL-1β in other settings is its capacity to "prime" cells for heightened responses to other stimuli, such as inflammasome-activating factors. Megli and colleagues showed that placental IL-1β production during midgestation is associated with increased IL-1β levels in serum and up-regulated expression of caspase-1 and IL-1β in circulating monocytes (Megli et al, 2020). Conditioned media from chorionic villous explants from pregnant women similarly primed the monocytes of nonpregnant women for up-regulated IL-1β, caspase-1, and NLRP3 expression.…”
Section: Trophoblast Il-1β Primes Maternal Monocytesmentioning
confidence: 99%
“…SYNs are reported to recognize pathogens via Toll-like receptors and RIG-I-like receptors (Koga and Mor, 2008), but their capacity to sense microbes or cell stress via the inflammasome was unknown. To investigate the mechanism underpinning cytokine production by chorionic villi, Megli et al (2020) performed detailed RNA sequencing analyses of trophoblasts isolated from chorionic villi. Indeed, midgestation trophoblasts expressed high levels of inflammasome-associated molecules such as caspase-1, NLRP3, IL-1β, and IL-18.…”
Section: The Placental Nlrp3 Inflammasome Generates Cytokines During mentioning
confidence: 99%
See 3 more Smart Citations